2021
DOI: 10.3390/plants10101976
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infections by Fusarium circinatum and Phytophthora spp. on Pinus radiata: Complex Phenotypic and Molecular Interactions

Abstract: This study investigated the complex phenotypic and genetic response of Monterey pine (Pinus radiata) seedlings to co-infections by F. circinatum, the causal agent of pine pitch canker disease, and the oomycetes Phytophthora xcambivora and P. parvispora. Monterey pine seedlings were wound-inoculated with each single pathogen and with the combinations F. circinatum/P. xcambivora and F. circinatum/P. parvispora. Initially, seedlings inoculated only with F. circinatum showed less severe symptoms than seedlings co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…inhibited by LABs isolated from olive drupes, such as A. alternata, C. acutatum, C. gloeosporioides, F. oxysporum and Ph. nicotianae, are very polyphagous pathogens (Aloi et al, 2021;Biasi et al, 2016;Dean et al, 2012;Kamali-Sarvestani et al, 2022;Kamoun et al, 2015;Riolo et al, 2021) Colletotrichum species, but P. nordicum was an exception as its sensitivity to CFSs of most bacterial isolates was even lower than the sensitivity showed by Colletotrichum species. This sensitivity of P. nordicum to fermentates of LABs is consistent with the results of Guimarães et al (2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…inhibited by LABs isolated from olive drupes, such as A. alternata, C. acutatum, C. gloeosporioides, F. oxysporum and Ph. nicotianae, are very polyphagous pathogens (Aloi et al, 2021;Biasi et al, 2016;Dean et al, 2012;Kamali-Sarvestani et al, 2022;Kamoun et al, 2015;Riolo et al, 2021) Colletotrichum species, but P. nordicum was an exception as its sensitivity to CFSs of most bacterial isolates was even lower than the sensitivity showed by Colletotrichum species. This sensitivity of P. nordicum to fermentates of LABs is consistent with the results of Guimarães et al (2018).…”
Section: Discussionmentioning
confidence: 97%
“…oleae were grown on Oat Meal Agar (OMA, Thermo Fisher, Waltham, Massachusetts, USA) at 22°C in the dark for 7 days. Zoospore production was performed according to Aloi et al (2021). Zoospore concentration was determined with a Neubauer chamber and adjusted to 10 4 zoospores/mL.…”
Section: Fungal Inoculummentioning
confidence: 99%
“…Other authors have reported co-occurring fungi in hazelnuts in different geographic areas [17,34,35]. Co-occurring microorganisms of other pathosystems are catching the attention of scientists [36,37], and they have acquired increasing relevance due to climate change for mycotoxin-producing fungi [38][39][40]. In particular, the co-occurrence of Diaporthe with the Aspergillus section Flavi has safety relevance due to the large proportion of nuts that fail quality standards for human consumption, and especially in Europe [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Even though simultaneous infections by more than a single pathogen of the same genus or different genera in plants are frequent in natural conditions, the complex phenotypic and genetic responses of plants to multiple infections are still scarcely known. However, they are receiving increasing attention, and recent studies focused also on co-infections by species of Phytophthora [37,38].…”
Section: Discussionmentioning
confidence: 99%